2016
DOI: 10.1111/hae.13061
|View full text |Cite
|
Sign up to set email alerts
|

Management of congenital quantitative fibrinogen disorders: a Delphi consensus

Abstract: The results of this initiative should help clinicians in the difficult management of patients with congenital fibrinogen disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 44 publications
0
65
1
Order By: Relevance
“…26 Supplementary fibrinogen infusions are required in the postsurgical period to target fibrinogen levels at least >1 g L −1 until haemostasis is achieved and above 0.5 g L −1 until wound healing is complete. 26 Supplementary fibrinogen infusions are required in the postsurgical period to target fibrinogen levels at least >1 g L −1 until haemostasis is achieved and above 0.5 g L −1 until wound healing is complete.…”
Section: Effi C Ac Ymentioning
confidence: 99%
“…26 Supplementary fibrinogen infusions are required in the postsurgical period to target fibrinogen levels at least >1 g L −1 until haemostasis is achieved and above 0.5 g L −1 until wound healing is complete. 26 Supplementary fibrinogen infusions are required in the postsurgical period to target fibrinogen levels at least >1 g L −1 until haemostasis is achieved and above 0.5 g L −1 until wound healing is complete.…”
Section: Effi C Ac Ymentioning
confidence: 99%
“…Delphi methodology has been already proposed with success to reach a consensus in a variety of complex medical issues [e.g., see Ref. (2325)]. Delphi methodology has also been used in the tinnitus field (26).…”
mentioning
confidence: 99%
“…They reported that fibrinogen levels significantly increased after fibrinogen substitution therapy [19]. According to Casini et al [20], the following formula should be used to evaluate the amount of fibrinogen to be administered = (target fibrinogen level [g/L] -basal fibrinogen level) 9 0.043 9 ?? weight (kg) in patients suffering from afibrinogenemia or congenital hypofibrinogenemia.…”
Section: Discussionmentioning
confidence: 99%